Enhancing Employee Loyalty Through Management Support and Work-Life Balance: Evidence from Heavy Equipment Rental Companies - Hutabarat, Manda Putra; Putri, Zakiyah (Lentera Ilmu Nusantara, 2025)
This study aims to analyze the effect of management support and work-life balance on employee loyalty in a heavy equipment rental company in Cikarang. In the context of increasingly competitive industrial competition, employee loyalty is an important element in improving organizational performance and reducing turnover. This study use quantitative approach. The results of the study indicate that management support that includes effective communication, performance rewards, and structured career development has a positive impact on employee loyalty. In addition, a good work-life balance helps employees cope with work pressure and maintain a balance between personal life and work, which ultimately increases employee engagement with the company. Analysis using the SmartPLS method confirms the validity and high reliability of the research model. These findings provide practical implications for companies to design policies that support employee welfare, such as work flexibility and managerial training, in order to increase loyalty and business sustainability.